Isolated Avulsion of the Common Hepatic Duct from Blunt Abdominal Trauma - Victor W. Wong; Arvin Gee; Paul Hansen; Andrew Michaels (Case Reports in Surgery)
Isolated extrahepatic biliary tract injury following blunt abdominal trauma is rare. The underlying pathogenic mechanisms remain obscure, but include shear and/or compression forces on the biliary system. Associated morbidity rates are high and largely the result of delays in diagnosis. Imaging modalities commonly employed for diagnosis include ultrasonography, computed tomography, nuclear medicine, and magnetic resonance imaging. Percutaneous and endoscopic techniques have been used both for diagnosis and treatment. Treatment options are dictated by the stability of the patient and the extent of bile duct and concomitant injuries. In this paper, we discuss a case of isolated avulsion of the hepatic duct confluence following blunt trauma that was successfully managed with Roux-en-Y hepaticojejunostomy. To our knowledge, this specific injury pattern has not been previously reported.